A single chip FPGA-based cross-coupling multi-motor drive system - Amornwongpeeti, Sarayut (2015)
Often, the demand for optimal and harmonious operation of multi-motor control systems requires sharing of feedback information from one drive to other drives. From the point of view of controller implementa- tion, a multi-controller structure degrades the system integration and requires data communication among chips. The aim of this paper is to propose a fully integrated single chip solution for a cross-coupling multi-motor control system. The proposed speed controller with time-division multiplexing scheme can simplify the entire system, making possible the implementation on a single device. The experimental results confirm the implementation feasibility and the effectiveness of the proposed single chip system.